THE NOTHINGNESS OF THE GETTIER PROBLEM - Tom Eneji Ogar; Edor J. Edor (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
This work, “The Nothingness” of the Gettier Problem is an attempt to deconstruct the popularly held view that a fourth condition may be necessary for the Traditional Account of Knowledge otherwise known as JTB. Plato, it was who championed the traditional account of knowledge as justified Belief in response to the agitation of the skeptics notably Georgias and Protagoras. This tripartite account held sway until Edmund Gettier Challenged the position with his article “Is Justified True Belief Knowledge?” Since this challenge, scholars have tried to solve what has become known as the Gettier Problem by trying to fashion out a fourth condition to JTB. This work argues that the celebrated Gettier counter-examples in the challenge of the tripartite account is a "nothingness". The traditional account is rather fundamental in knowledge claim, hence any new vista in form of additional information on JTB should not invalidate it. The textual analysis was adopted as a method for this research.